The COVID-19 Pandemic and Gendered Division of Paid and Unpaid Work: Evidence from India - Ashwini Deshpande (Institute of Labor Economics (IZA), 2020)
Examining high frequency national-level panel data from Centre for Monitoring Indian Economy (CMIE) on paid work (employment), unpaid work (time spent on domestic work) and incomes, this paper examines the effects of the Covid-19 pandemic on the gender gaps in paid and unpaid work through the lockdown and recovery phases. The first month of the national lockdown, April 2020, saw a large contraction in employment for both men and women, where more men lost jobs in absolute terms. Employment has recovered by August 2020 for men. However, for women, the likelihood of being employed is 9.5 percentage points lower than that for men, compared to the pre-pandemic period. Men spent more time on housework in April 2020, but by August the average male hours had declined, though not to the pre-pandemic levels. Time spent with friends fell sharply for both men and women in April, to recover in August, but not to the pre-pandemic levels. The paper also examines available income data to find the sharpest contraction of incomes in the rural sector for both men and women.
Keywords: J1; J6; O53; 330; COVID-19; lockdown; employment; gender; time use; incomes; India